Recent development of mitochondrial metabolism and dysfunction in osteoarthritis - Guo, Pengchao; Alhaskawi, Ahmad; Adel Abdo Moqbel, Safwat; Pan, Zhijun (Frontiers in Pharmacology, 2025)
Osteoarthritis is a degenerative joint disorder characterized by cartilage degradation, synovial inflammation, and altered subchondral bone structure. Recent insights have identified mitochondrial dysfunction as a pivotal factor in OA pathogenesis, contributing to chondrocyte apoptosis, oxidative stress, and extracellular matrix degradation. Disruptions in mitochondrial dynamics, including impaired biogenesis, mitophagy, and metabolic shifts from oxidative phosphorylation to glycolysis, exacerbate cartilage damage by promoting the production of reactive oxygen species and matrix-degrading enzymes such as ADAMTS and MMPs. This review explores the molecular mechanisms underlying mitochondrial dysfunction in OA, emphasizing its role in cartilage homeostasis and inflammation. Furthermore, it highlights emerging therapeutic strategies targeting mitochondrial pathways, including antioxidants, mitophagy enhancers, and metabolic modulators, as potential interventions to mitigate disease progression, which offer promising avenues for advancing personalized and disease-modifying treatments in OA.